Effect of prostaglandin F2alpha, oxytocin and butylated hydroxytoluene on freezability of crossbred bull spermatozoa - ARANGASAMY, A; SINGH, L P; ANSARI, M R; RAWAL, C V S (The Indian Journal of Animal Reproduction, 2023)
Semen samples were collected from two crossbred bulls (HF x Hariana) and diluted in Tris with three combinations of ad tives i.e. prostaglandin F 2 a, oxytocin and butylated hydroxytoluene and frozen in liquid nitrogen. The sperm motility, livability and infact acrosome percentage were evaluated at pre-freeze and postfreeze stages. Except prostaglandin F 2 a, the other additives showed no significant difference in motility after dilution vs control. At pre-freeze stage, sperm motility differed significantly between treated and control groups. At post-freeze stage, sperm motility and livability differed significantly between treatment and control groups. Among the additives PGF 2a performed better than oxytocin and BHT in maintaining higher motility, livability and acrosomal integrity in post-thaw semen.